Hello, Can we write a summation of exponentials, as a multiplication of exponentials? Regards
Jun 12, 2009 #1 EngWiPy 1,367 61 Hello, Can we write a summation of exponentials, as a multiplication of exponentials? Regards
Jun 12, 2009 #2 CompuChip Science Advisor Homework Helper 4,306 49 Only like [tex]e^a e^b = e^{a + b}[/tex] There is no such rule as [tex]e^a + e^b = e^{a b}[/tex] or something like that.
Only like [tex]e^a e^b = e^{a + b}[/tex] There is no such rule as [tex]e^a + e^b = e^{a b}[/tex] or something like that.
Jun 13, 2009 #3 CRGreathouse Science Advisor Homework Helper 2,824 0 Best I can do is e^a + e^b = e^a * (1 + e^(b-a)).